The Effect of Students’ Trust in Instructors on Students’ Class Participation and School Engagement: Example of Faculty of Sports Sciences - Çetin Işık; Ali Erdoğan; Hatice Deveci Şirin; Erkan Faruk Şirin (Türk Spor ve Egzersiz Dergisi)
Trust in instructors is one of the most important variables affecting university reform and students' college life. The research focused on the trust in the instructors which is considered to have an influence on class participation and school engagement. Accordingly, the aim of this study is to examine the relationship between trust in faculty members and class participation and school engagement with regard to faculty of sport sciences. The study group in this research consisted of y 552 students (194 female, 358 male) – voluntary participation - who were studying in the physical education and sports teaching, sports management, coaching education and recreation departments in the Faculty of Sports Sciences at Selçuk University. The study was carried out through a quantitative approach. Student Trust in Professors Scale, Student Engagement Scale and School Engagement to Higher Education Scale were used in order to collect data in the study. Study data were analyzed via arithmetic mean, standard deviation, confirmatory factor analysis, correlation analysis and structural equation modeling. As a consequence of this study, positive relationship was found between students’ trust in the instructors and students’ participation in the course and their school engagement. Moreover, the study shows that the positive effect of students’ trust in the instructor on school engagement is more effective than its effect on their participation in the course.